Research on the Identification and Development of Sport Talent. - Wheeler, R. T.
Research is in progress on the development of a comprehensive, multi-disciplinary model for the identification and development of sport talent in South Africa. The study commences with the introduction of a "sport for all" programme, introducing children aged 5 to 12yrs to up to 16 sports codes. The idea is to use game modification and games that lead to competencies for these sports. During this programme talent is detected by coaches and children able to provide comments. The second phase encompasses the facilitating of the development of talented athletes aged 13 to 16yrs. These children are still at school and provision must be made for the introduction of standardized programmes whereby skills and competencies can be developed and instructors and coaches trained. The third phase is the investigation into a model for the preparation of the high performance athlete for entrance into senior, competitive sport and a career after sport.